2015
DOI: 10.1002/ejlt.201400430
|View full text |Cite
|
Sign up to set email alerts
|

A novel source of dihomo‐γ‐linolenic acid: Possibilities and limitations of DGLA production in the high‐density cultures of the Δ5 desaturase‐mutant microalga Lobosphaera incisa

Abstract: The D5 desaturase mutant (P127) of the microalga Lobosphaera incisa is a promising organism for large-scale production of the valuable LC-PUFA dihomo-g-linolenic acid (DGLA, 20:3 n-6). We examined the potential of P127 for DGLA production under nitrogen (N) starvation conditions, triggering the deposition of DGLA in triacylglycerols, and developed a strategy for optimization of the DGLA productivity in highdensity cultures. Towards this end, the effects of initial biomass concentration (1, 2, and 4 g L À1 ) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In this work, zebrafish were fed with experimental diets, in which a certain fraction of the original feed (7.5 and 15%) was replaced with broken biomasses of two strains of the oleagenous microalga L. incisa . The two strains of this microalga accumulate n -6 LC-PUFA as the major component of triacylglycerols, in particular under nitrogen starvation ( 23 , 37 ). Hence, n -6 LC-PUFA-enriched triacylglycerols were the major source of dietary ARA and DGLA, in the WT- and MUT-supplemented diets, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, zebrafish were fed with experimental diets, in which a certain fraction of the original feed (7.5 and 15%) was replaced with broken biomasses of two strains of the oleagenous microalga L. incisa . The two strains of this microalga accumulate n -6 LC-PUFA as the major component of triacylglycerols, in particular under nitrogen starvation ( 23 , 37 ). Hence, n -6 LC-PUFA-enriched triacylglycerols were the major source of dietary ARA and DGLA, in the WT- and MUT-supplemented diets, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no reports of studies on DGLA dietary supplementation in fish, largely due to limitations in the availability of this rare LC-PUFA. In this context, the microalga Lobosphaera incisa wild type (WT) and its Δ5-desaturase mutant P127 (MUT) are unique photosynthetic sources for ARA and DGLA, respectively ( 22 , 23 ), whose potential in aquaculture nutrition is yet to be explored. Microalgae are an emerging resource for biochemical diversity and various health-promoting ingredients, such as LC-PUFA, carotenoids, exopolysaccharides and more.…”
Section: Introductionmentioning
confidence: 99%
“…1). Several studies have already reported an increase in specific growth rates with increasing light supplies (Abu-Ghosh et al 2015b, Ota et al 2015, Gonc ßalves et al 2016). However, in the light-temperature matrix, there was a strong interaction in which the growth dependency on light differed significantly (P < 0.005) between growth temperatures.…”
Section: Resultsmentioning
confidence: 93%
“…Several studies have already reported an increase in specific growth rates with increasing light supplies (Abu‐Ghosh et al. 2015b, Ota et al. , Gonçalves et al.…”
Section: Resultsmentioning
confidence: 98%